Video transmission over an enhancement approach of IEEE802.11e - Jama, Abdirisaq Mohammed; Khalifa, Othman Omran; Ahmed, Diaa Eldein Mustafa (International Journal of Computer Applications Technology and Research, 2015)
Multimedia Video transmission is over Wireless Local Area Networks is expected to be an important component of many emerging multimedia applications. However, Wireless networks will always be bandwidth limited compared to fixed networks due to background noise, limited frequency spectrum, and varying degrees of network coverage and signal strength One of the critical issues for multimedia applications is to ensure that the Quality of Service (QoS) requirement to be maintained at an acceptable level. Modern mobile devices are equipped with multiple network interfaces, including 3G/LTE WiFi. Bandwidth aggregation over LTE and WiFi links offers an attractive opportunity of supporting bandwidth-intensive services, such as high-quality video streaming, on mobile devices. Achieving effective bandwidth aggregation in wireless environments raises several challenges related to deployment, link heterogeneity, Network congestion, network fluctuation, and energy consumption. In this work, an overview of schemes for video transmission over wireless networks is presented where an acceptable quality of service (QoS) for video applications required realtime video transmission is achieved.